Lymphocytes Protect Cortical Neurons Against Excitotoxicity Mediated by Kainic Acid, an in vitro Model for Neurodegeneration - Shrestha, R; Millington, O; Brewer, J; Bushell, T (Kathmandu University Medical Journal, 2015)
Background Neurodegenerative disease is a progressive loss of neurons from the central nervous system (CNS). Various conditions have been implicated for such conditions including ageing, inflammation, stress and genetic predisposition. Recently, studies have linked neurodegeneration with inflammation. Some studies have suggested the harmful effect of immune response while others have argued its neuroprotective role in neurodegeneration of the CNS. However, the precise role of inflammation and immune cells in such condition is still not clear. Objective To investigate the role of lymphocytes in neurodegeneration of the CNS and determine the underlying mechanism. Method We have used 4-7 days old mouse pups (C57Bl6) to prepare organotypic slice cultures which were cultured for 13-15 days prior to experiment. To induced cell death kainic acid was used and considered as an in vitro model for neurodegeneration. Lymphocytes were obtained from peripheral lymph nodes of 5-10 weeks old adult mouse which were used in the current study. Propidium iodide was used as a fluorescent dye to determine cell death in brain slice cultures. Result Lymphocytes do not induce cell death in slice cultures in the absence of any toxic insult whereas, after applying toxic insult to the slice cultures using kainic acid, lymphocytes show neuroprotection against such insult. Similarly, purified non-activated and purified activated T cells along with T cells depleted lymphocyte preparation also exhibit neuroprotection against kainic acid-induced cell death. We further, have demonstrated that the observed neuroprotection is contact-independent and soluble mediators released from lymphocytes are responsible for the observed neuroprotection. Moreover, our study has revealed that soluble mediators exhibiting neuroprotection act via astrocytes. Conclusion Lymphocyte preparations are neuroprotective and the observed neuroprotection is contact-independent. Soluble mediators released from lymphocytes are responsible for the observed neuroprotection. DOI: http://dx.doi.org/10.3126/kumj.v11i2.12488 Kathmandu University Medical Journal Vol.11(2) 2013: 132-138